Perencanaan Strategis Sistem Informasi (Studi Kasus PDAM JAYA) - Muhammad Firdaus (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
Rapid development of information technology and communication allows company management to better optimize their service quality. Based on the result of study in PDAM JAYA (Perusahaan Daerah Air Minum JAkarta RaYA), the delivery of improperly prepared customers’ summary reports is an particular issueraising due to inadequate IT facilities. Strategic Planning for Information System is used to optimally support the function and role of the company in monitoring and controlling two Private Partners. Methodology used will apply some steps from Tozer framework, while some other analysis methods used to support this research are : SWOT (Strengths, Weaknesses, Opportunities, and Threats), Critical Success Factors (CSFs), McFarlan’s Application Portfolio, Value Chain, dan PEST (Political, Economic, Socialand Technological). The result of this research will provide an Information System / Technology strategic solution with technical supportsfor IT facilities suitable to use by the company so that the companycan efficientlyfulfill its needs in the future and rearrange the information technology architecture by adding a number of other supporting facilitiesin order to anticipate the increase of online data capacity management in Private Partner